GPR98 mutations cause Usher syndrome type 2 in males. Issue 4 (8th April 2009) - Ebermann, I; Wiesen, M H J; Zrenner, E; Lopez, I; Pigeon, R; Kohl, S; Löwenheim, H; Koenekoop, R K; Bolz, H J
Abstract : Mutations in the large GPR98 gene underlie Usher syndrome type 2C (USH2C), and all patients described to date have been female. It was speculated that GPR98 mutations cause a more severe, and eventually lethal, phenotype in males. We describe for the first time two male patients with USH2 with novel GPR98 mutations. Clinical characterization of a male patient and his affected sister revealed a typical USH2 phenotype in both. GPR98 may have been excluded from systematic investigation in previous studies, and the proportion of patients with USH2C probably underestimated. GPR98 should be considered in patients with USH2 of both sexes.